Dehydrated Kitchen Waste as a Feedstuff for Laying Hens - Kojima, Sadao (International Journal of Poultry Science, 2005)
An experiment was conducted to determine the effects of dehydrated kitchen waste (DKW) product as a feedstuff for laying hens. Fresh food wastes of a retirement house were prepared for the experiment. This was mostly leftover food, plate scrapings and cooking residue. The kitchen waste was blended and dried by the temperature in the heater set at 80 to 85oC in which the product temperature reached 60 to 65oC. The DKW product contained 12.24% moisture, 15.14% Crude Protein, 5.33% crude fat, 2.34% crude fiber, 5.26% ash, 2.82% Ca, 0.29% P and 0.31% Na. A total of 40 laying hens were fed a control diet (diet 1) or one of three diets containing 12.5% DKW (diet 2); 25.0% DKW (diet 3); 50.0% DKW (diet 4). There were 10 birds per treatment and 5 birds per replicate. The diet with 50.0% DKW decreased egg weight (P< 0.001). There were no significant differences in egg production rate and feed conversion. The birds fed diets 1, 2 and 3 increased body weights during feeding period. The eggshell strength tended to weaken with increased DKW. The lightness (L*) of eggshell color was significantly higher with increasing DKW (P< 0.001), and the reverse was true for the redness (a*) of eggshell color. Roche color fan values decreased as DKW content increased. These results indicate that dehydrated kitchen wastes contains the nutritional value and that may be useful as feedstuffs for laying hens.